Instructional scaffolding in STEM education : strategies and efficacy evidence - Belland, Brian R (Springer Open, 2017)
Synthesizing research on scaffolding and scaffolding-related interventions in STEM (science, technology, engineering, and mathematics) education, this book uses meta-analysis to assess their effect, and includes detailed descriptions of the background theory.